Frecuencia de inestabilidad hemodinámica utilizando anestesia total intravenosa en adultos neuroquirúrgicos - Castillo Benites, Carlos Miguel (2016)
BACKGROUND: Total intravenous anesthesia is a general anesthesia technique in which drugs exclusively administered intravenously in the absence of any anesthetic agent inhaled. It has been successfully used in neurosurgery, because it has a minimal effect on intracerebral pressure and provide good hemodynamic stability OBJECTIVE: To determine the frequency of instability mean arterial pressure in adults neurosurgical using total intravenous anesthesia. MATERIALS AND METHODS: Transversal and descriptive study of 11 adults between 17-65 years of age recruited by random sampling underwent neurosurgery operating room HRDT. Hemodynamic instability was determined when the values of mean arterial pressure were not found within parameters established in previous studies. RESULTS: 27% of hemodynamic instability was found during the anesthetic induction, of which 33.3% are hypertensive events and 66.7% of hypotensive events, without mixed events; however it not presented hemodynamic instability during the anesthetic maintenance. Variability in MAP was recorded on induction between 50 and 106.7 mmHg and maintenance was between 60 and 107 mmHg. CONCLUSIONS: 27% of patients had hemodynamic instability events during anesthetic induction; however, variations in MAP, failed to theoretically affect ranges cerebral autoregulation.